PREFERENSI KONSUMEN TERHADAP MINUMAN FERMENTASI: STUDI KOMPARATIF ANTAR KELOMPOK UMUR - Rasmikayati, Elly; Yudha, Eka Purna; Saefudin, Bobby Rachmat (Fakultas Pertanian Universitas Janabadra, 2026)
Fermented beverages have become increasingly popular as functional products that offer health benefits, particularly in improving digestive function and enhancing body immunity. However, the successful marketing of these products largely depends on understanding consumer preferences, which may vary according to demographic characteristics, especially across different age groups. This study aims to analyze the differences in consumer preferences for five key attributes of fermented beverages—taste, price, packaging, packaging volume, and serving temperature—across four age categories: children, adolescents, adults, and the elderly. The research employed a quantitative survey method involving 145 respondents. Data were analyzed using frequency distribution tables, boxplot analysis, and the Kruskal–Wallis test. The results revealed that, in general, consumers preferred sweet and sour tastes in balanced proportions, favored products priced above Rp 10,000, and tended to prefer plastic packaging, although interest in glass packaging has begun to emerge. The most preferred packaging volume was 100–250 ml, and cold serving temperature remained the dominant preference. Statistical tests showed significant differences in preferences for price, packaging, and serving temperature across age groups (p < 0.05). Children preferred lower prices, plastic packaging, and cold beverages, whereas adults and the elderly showed a stronger preference for glass packaging, larger volumes, and warmer serving temperatures. Conversely, no significant differences were found in taste and packaging volume preferences (p > 0.05).